Two-gene control of T-helper cell induction. - Erb, P; Meier, B; Feldmann, M (1976)
At the present moment the number of genes that have an influence on helper cell induction is not yet known. The results of researches referred to here speak in favour of at least 2 I regions of genes participating in it. (Schmid - Munchen)